Pembelajaran Anak Usia Dini dengan Pendekatan Proyek - Christianti, Martha (Dinamika Pendidikan, 2015)
Project approach is one approach that combines the principles of early childhood learning that is playing while learning and child-centered learning. In this approach, the emphasis on the application of learning skills; the child's motivation to learn appears to be intrinsically rather than extrinsically; interest and involvement of children increased effort and motivation to find out about something not because of the necessity of a teacher or wish to obtain a specific reward; children are given the freedom to choose activities that have been provided and tried to find answers to the challenges of a more appropriate rathe~ than the dominance of the teacher in selecting learning activities, providing :teachingmaterials at the appropriate level of teaching; child is proficient, the teacher helps develop the skills that exist in the child, not the teacher as expert view children as individuals who have weaknesses, and children share responsibility with teachersfor learning and achievement rather than teachers are responsible for learning and achievement is a necessity that must; be achieved by the children. This approach is to develop all aspects of t~e development of religious and moral values, physical, cognitive, language, social and emotional in an integrated, not separated (fragmented). Key word: Project al!proach,playing while learning, child-centered